Co-transfection of decorin and interleukin-10 modulates pro-fibrotic extracellular matrix gene expression in human tenocyte culture - Abbah, Sunny A. (Sci Rep, 2016)
Extracellular matrix synthesis and remodelling are driven by increased activity of transforming growth factor beta 1 (TGF-β1). In tendon tissue repair, increased activity of TGF-β1 leads to progressive fibrosis. Decorin (DCN) and interleukin 10 (IL-10) antagonise pathological collagen synthesis by exerting a neutralising effect via downregulation of TGF-β1. Herein, we report that the delivery of DCN and IL-10 transgenes from a collagen hydrogel system supresses the constitutive expression of TGF-β1 and a range of pro-fibrotic extracellular matrix genes.